2011
DOI: 10.1101/gr.114272.110
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun proteomics aids discovery of novel protein-coding genes, alternative splicing, and “resurrected” pseudogenes in the mouse genome

Abstract: Recent advances in proteomic mass spectrometry (MS) offer the chance to marry high-throughput peptide sequencing to transcript models, allowing the validation, refinement, and identification of new protein-coding loci. We present a novel pipeline that integrates highly sensitive and statistically robust peptide spectrum matching with genome-wide protein-coding predictions to perform large-scale gene validation and discovery in the mouse genome for the first time. In searching an excess of 10 million spectra, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 76 publications
(78 reference statements)
4
125
0
3
Order By: Relevance
“…Recent studies suggested that pseudogenes may be transcribed and even translated to fragmented peptides but may lack properly folded structures (30,31), thus unnecessarily consuming energy from the bacteria. We did not find a pattern of growth-dependent regulation of the phage-carried virulence genes.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggested that pseudogenes may be transcribed and even translated to fragmented peptides but may lack properly folded structures (30,31), thus unnecessarily consuming energy from the bacteria. We did not find a pattern of growth-dependent regulation of the phage-carried virulence genes.…”
Section: Resultsmentioning
confidence: 99%
“…One example is the reprocessing of proteomics datasets to improve genome annotation in so‐called proteogenomics approaches. For example, Brosch et al reprocessed shotgun proteomics data from PeptideAtlas to discover novel protein‐coding genes and to improve gene annotation in the mouse genome 86. At the time, they found alternatively spliced translations from 53 genes along with ten entirely novel protein‐coding genes.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudogenes are classified according to their mode of formation: either by mRNA retroinsertion (processed pseudogenes), gene duplication (unprocessed pseudogenes), or by the inactivation of functional genes (unitary pseudogenes). While pseudogenes do not contain an intact or translated CDS, at least 9% of human pseudogenes are transcribed (Pei et al 2012), and there is evidence that pseudogene loci can gain new functionality via ''resurrection'' (Brosch et al 2011;Pei et al 2012;Johnsson et al 2013). Finally, GENCODE contains numerous categories of small RNA, which are beyond the scope of this article.…”
Section: The Capture and Annotation Of Transcript Modelsmentioning
confidence: 99%
“…Second, both the processing of the spectra and the subsequent genomic mapping are complex, computationally intensive techniques. In particular, peptide to genome mappings may suffer from a high false positive rate unless rigorous methods are used (a situation confounded by the occurrence of AS) (Tanner et al 2007;Brosch et al 2011;Ezkurdia et al 2012).…”
Section: The Annotation Of Cdss Based On Proteomics Datamentioning
confidence: 99%
See 1 more Smart Citation